THE LEVELS OF QUESTIONS USED IN THE ENGLISH TEXTBOOK ENTITLED â€œSTOP BULLYING NOWâ€FOR THE XI GRADE OF SENIOR HIGH SCHOOL - Wahyuni, Ketut Budi (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
Reading comprehension in Indonesian students is very weak. It is proven by Pisa 2018, a result which states that from a comparison between science, mathematics, and reading comprehension, Indonesian students are ranked 74th in the sixth from bottom. This article aims to analyze the level of questions used in an English textbook entitled "Stop Bullying Now" for class XI SMA published by the Ministry of Education and Culture of the Republic of Indonesia in 2017. This analysis uses Barrett's taxonomy to test reading comprehension. Questions in the book with content analysis of qualitative research. Based on Barrett's taxonomy, there are five levels of reading comprehension questions: literal comprehension, reorganization, inferential, evaluation, and appreciation. The results showed that the level of literal understanding (7.45%), reorganization (0 %), inferential (39.36%), evaluation (36.17%), and appreciation (17.02%). This shows that the higher-level comprehension is dominant over lower-level comprehension, but the level is not evenly distributed in all texts. The results of this study can provide an overview of the level of reading comprehension questions used in the English textbook entitled "Stop Bullying Now," which is helpful for teachers as a guide in learning English reading comprehension.